Fluorouracil and dose-dense adjuvant chemotherapy in patients with early-stage breast cancer (GIM2): end-of-study results from a randomised, phase 3 trial. Issue 12 (December 2022) - Del Mastro, Lucia; Poggio, Francesca; Blondeaux, Eva; De Placido, Sabino; Giuliano, Mario; Forestieri, Valeria; De Laurentiis, Michelino; Gravina, Adriano; Bisagni, Giancarlo; Rimanti, Anita; Turletti, Anna; Nisticò, Cecilia; et al.
Summary: Background: Previous analyses of the GIM (Gruppo Italiano Mammella) 2 study showed that addition of fluorouracil to epirubicin, cyclophosphamide, and paclitaxel in patients with node-positive early breast cancer does not improve outcome, whereas dose-dense chemotherapy induces a significant improvement in both disease-free survival and overall survival as compared with a standard schedule. Here, we present long-term results of the study. Methods: In this 2 × 2 factorial, open-label, randomised, phase 3 trial, we enrolled patients aged 18–70 years with operable, node-positive, breast cancer with Eastern Cooperative Oncology Group performance status of 0–1 from 81 hospitals in Italy. Eligible patients were randomly allocated (1:1:1:1) to one of the four following study groups: four cycles of standard-interval intravenous EC (epirubicin 90 mg/m 2 and cyclophosphamide 600 mg/m 2 ) on day 1 every 3 weeks, followed by four cycles of intravenous paclitaxel (175 mg/m 2 ) on day 1 every 3 weeks (q3EC-P group); four cycles of intravenous FEC (fluorouracil 600 mg/m 2, epirubicin 90 mg/m 2, and cyclophosphamide 600 mg/m 2 ) on day 1 every 3 weeks, followed by four cycles of intravenous paclitaxel (175 mg/m 2 ) on day 1 every 3 weeks (q3FEC-P group); dose-dense EC-P regimen, with the same doses and drugs as the q3EC-P group but administered every 2 weeks (q2EC-P group); and the dose-dense FEC-P regimen, with the same doses and drugs as the q3FEC-P group but given every 2 weeks (q2FEC-P). Randomisation, with stratification by centre, with permuted blocks of size 12, was done with a centralised, interactive, internet-based system that randomly generated the treatment allocation. The primary endpoint was disease-free survival in the intention-to-treat population, comparing different chemotherapy schedule (dose-dense vs standard-dose intervals) and regimen (FEC-P vs EC-P). Safety population included all patients that received at least one dose of any study drug according to the treatment received. This trial is registered with ClinicalTrials.gov, NCT00433420, and is now closed. Findings: Between April 24, 2003, and July 3, 2006, 2091 patients were randomly assigned to treatment: 545 to q3EC-P, 544 to q3FEC-P, 502 to q2EC-P, and 500 to q2FEC-P. 88 patients were enrolled in centres providing only standard interval schedule and were assigned only to q3FEC-P and q3EC-P; thus, 2091 patients were included in the intention-to-treat analysis for the comparison of EC-P (1047 patients) versus FEC-P (1044 patients) and 2003 patients were included in the intention-to-treat analysis for the comparison of dose-dense (1002 patients) versus standard interval analysis (1001 patients). After a median follow-up of 15·1 years (IQR 8·4–16·3), median disease-free survival was not significantly different between FEC-P and EC-P groups (17·09 years [95% CI 15·51–not reached] vs not reached [17·54–not reached]; unadjusted hazard ratio 1·12 [95% CI 0·98–1·29]; log-rank p=0·11). Median disease-free survival was significantly higher in the dose-dense interval group than the standard-interval group (not reached [95% CI 17·45–not reached] vs 16·52 [14·24–17·54]; 0·77 [95% CI 0·67–0·89]; p=0·0004). The most common grade 3–4 adverse events were neutropenia (200 [37%] of 536 patients in the q3EC-P group vs 257 [48%] of 533 in the q3FEC-P group vs 50 [10%] of 496 q2EC-P vs 97 [20%] of 492) and alopecia (238 [44%] vs 249 [47%] vs 228 [46%] vs 235 [48%]). During extended follow-up, no further grade 3–4 adverse events or deaths related to toxic-effects were reported. Treatment-related serious adverse events were reported in nine (2%) patients in the q3EC-P group, seven (1%) in the q3FEC-P group, nine (2%) in the q2EC-P group, and nine (2%) in the q2FEC-P group. No treatment-related deaths occurred. Interpretation: Updated results from the GIM2 study support that optimal adjuvant chemotherapy for patients with high-risk early breast cancer should not include fluorouracil and should use a dose-dense schedule. Funding: Bristol-Myers Squibb, Pharmacia, Dompè Biotec Italy, Italian Ministry of Health, Fondazione Italiana per la Ricerca sul Cancro, and Alliance Against Cancer.